Can public service motivation increase work engagement?—A meta-analysis across cultures - Ding, Mengxiao; Wang, Chengli (Frontiers in Psychology, 2023)
Civil servants' work engagement is an essential topic in human resource management research in the public sector. To explore the effects, mechanisms of action, and boundary conditions of public service motivation on civil service engagement, this paper utilizes a meta-analytic approach to analyze 31 independent samples from 10 countries through literature search, screening, and coding. The result showed a significant positive relationship between public service motivation and work engagement with no possibility of publication bias. The regulatory effect test through Hofstede's model revealed that the dimensions of power distance, individualism/collectivism, long-term orientation/short-term orientation, and self-indulgence and restraint significantly moderate the relationship between public service motivation and work engagement. This study provides a clear explanation for understanding the relationship between public service motivation and work engagement from a cross-cultural perspective and provides some theoretical implications for improving public servants' involvement in the future.